Emphysematous pyelonephritis within a horseshoe kidney - Amit Tuli; Faireena Singh; Kim Jacob Mammen (Wolters Kluwer Medknow Publications, 2017)
Association of emphysematous pyelonephritis (EPN) with horseshoe kidney is rare. It is a life-threatening condition with variable mortality. Historically, the treatment consisted of early nephrectomy. One such patient managed conservatively by placement of percutaneous drainage (PCD) and appropriate antibiotic coverage, is reported. This patient responded well to the conservative approach of treatment by insertion of PCD under computed tomography guidance. Hence, insertion of PCDs is an effective way of treating EPN.